How is the Company’s Financial Performance After Merger with the Economic Value Added Approach? - Ibnu Muttaqin; Kharis Fadlullah Hana (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
The objective of this research is to find out whether the merger decision is correct with more appropriate indicators compared to other financial indicators. The comparison of Economic Value Added (EVA) values, both between Islamic banks before merger and before and after merger. Through a quantitative approach with data two years before merger, from 2019-2020 and two years after the merger from 2021-2022. Paired samples t-test was used as a statistical approach. It can be concluded from the results of the different tests before merger, there is no significant difference between BRIS and BNIS, while between BSM and BRIS and BNIS there is a significant difference with the EVA value of BSM not being better than BRIS and BNIS. Furthermore, in the pre- and post-merger it was found that the EVA values were significantly different, with the average EVA value after merger being better than before. Refer ot this study, it can be concluded that the decision of merger is effective.